Relationship Between The Physical Environment of House and The Incidence of Acute Respiratory Infections in Children Under Five in Ngada Regency - Trince Bura; Soni Doke; Masrida Sinaga (Lontar : Journal of Community Health, 2021)
Acute Respiratory Infections (ISPA) is the highest cause of morbidity and mortality among children under five in Indonesia, especially in East Nusa Tenggara. The purpose of this study was to determine the relationship between the physical environment of the house and the incidence of ISPA in toddlers in the working area of ​​Aimere Public Health Center. The type of research used was analytical survey research with a cross-sectional study design. This study's population was all toddlers listed in the Aimere Puskesmas register, as many as 783 toddlers. The sample in this study was some of the toddlers recorded in the Aimere Puskesmas register, totaling 265 toddlers. The sampling technique in this study was random sampling. This study used the Chi-Square test for data analysis. The results of this study indicated that there was a relationship between occupancy density (p= 0.020), ventilation area (p= 0.023), floor type (p= 0.000), wall type (p= 0.000), indoors lighting (p= 0.011) with the incidence of ISPA in toddlers. Health promotion efforts and actions are needed to improve environmental health, especially housing conditions, to prevent ISPA in children under five.